The evaluation of English for General Academic Purposes (EGAP) course in an Indonesian university - Floris, Flora Debora (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2011)
This paper presents an internal evaluation on English for General Academic Purposes (EGAP) subject which is developed by the English Language Teaching Center (ELTC) from a private university in East Java, Indonesia. The research was conducted to elicit feedback on the effectiveness of English for General Academic Purposes (EGAP). The presented data were obtained from questionnaires, group interviews, classroom observations, and the students’ final scores. There were 124 students and 6 lecturers involved in this small-scale research. Therefore, this paper is intended to describe the interesting facts of the study.